Pengaruh Pendapatan Per Kapita, Inflasi dan Kurs Terhadap Impor Barang Konsumsi di Indonesia Periode 2000 – 2022 - Ramadhanis, Alvira Cindy; Anward, Ryan Juminta (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
As a country with a large population, Indonesia shows an increasing trend of imports of consumer goods every year. This can further restrict the growth of the domestic industrial sector, so it is important to analyze the factors that influence imports of consumer goods to establish the right policy. The purpose of this research is to analyze how imports of consumer goods are affected by per capita income, inflation and exchange rates in short and long term period 2000 – 2022. Previous research shows diverse results regarding the effect of inflation on imports of consumer goods. Some research also focusses on imports in general so research that specifically discusses imports of consumer goods is still limited. This research attempts to analyze by using analysis method that is the Error Correction Model. Based on analysis, simultaneously both in short and long term imports of consumer goods are significantly affected by per capita income, inflation and exchange rates. Partially, per capita income and inflation have a significant effect on imports of consumer goods in the short term. Then, in the longer term, per capita income and exchange rate have a significant effect on imports of consumer goods. The variable in this study that has a dominant influence on imports of consumer goods in Indonesia is per capita income.